1999
DOI: 10.1159/000056521
|View full text |Cite
|
Sign up to set email alerts
|

Specific Uptake of Alpha-Fetoprotein and Albumin by Rat Morris 7777 Hepatoma Cells

Abstract: Alpha-fetoprotein (AFP) is a major globulin of embryonic plasma and a physiological carrier of unesterified fatty acids. In the present work, we have characterized the interaction of AFP and albumin, a major serum protein of adult mammals which presents numerous biochemical analogies with AFP, with the plasma membrane of the rat Morris 7777 hepatoma cells. Time course analysis of the uptake of AFP and albumin by these cells showed a saturable profile at 4°C and 37°C. Saturable binding of 125I-AFP or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Following uptake, AFP was observed in coated pits of the cell membrane and was then tracked to vesicles, multivesicular bodies, and the trans-Golgi network surrounding the nucleus (Table 1) [18,22]. A series of studies subsequently showed that the property of AFP uptake was present in neoplastic cells such as breast/mammary carcinomas, hepatomas, neuroblastomas, lymphomas, and T and B cell malignancies [17,19,22,33,34] (Table 2). Those studies and others strongly supported the presence of an AFP cellsurface receptor as an integral cell membrane protein.…”
Section: Uptake Of Afp By Cancer Cellsmentioning
confidence: 99%
“…Following uptake, AFP was observed in coated pits of the cell membrane and was then tracked to vesicles, multivesicular bodies, and the trans-Golgi network surrounding the nucleus (Table 1) [18,22]. A series of studies subsequently showed that the property of AFP uptake was present in neoplastic cells such as breast/mammary carcinomas, hepatomas, neuroblastomas, lymphomas, and T and B cell malignancies [17,19,22,33,34] (Table 2). Those studies and others strongly supported the presence of an AFP cellsurface receptor as an integral cell membrane protein.…”
Section: Uptake Of Afp By Cancer Cellsmentioning
confidence: 99%
“…Many hepatocarcinoma cell lines, such as Bel7402, HepG2 and SMMC‐7721, can express AFP mRNA and protein and AFP receptors exist on membranes of these cells. So AFP and its receptors on the membranes form autocrine loops that play an important role in maintaining the growth of hepatocarcinoma cells 4,5 . The importance of AFP to hepatocarcinoma cells also means that suppression or influence of AFP expression and its biological activity may be a new method to inhibit the growth of hepatocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…So AFP and its receptors on the membranes form autocrine loops that play an important role in maintaining the growth of hepatocarcinoma cells. 4,5 The importance of AFP to hepatocarcinoma cells also means that suppression or influence of AFP expression and its biological activity may be a new method to inhibit the growth of hepatocarcinoma cells. Many results indicate that downregulation of AFP expression is able to induce the growth inhibition of hepatocarcinoma cells.…”
Section: W E Are Particularly Interested In Afp Becausementioning
confidence: 99%
See 2 more Smart Citations